The impact of Covid-19 on women's experiences of and through football in Buenos Aires - Román Lozano, J.; Santino, M.; Wood, D. (Frontiers in Physiology, 2021)
This research report explores the impact of Covid-19 on women's football in Buenos Aires. The suspension of all forms of football in Argentina as part of the country's hard lockdown measures threatens to undo significant gains made in women's football in recent years. By focussing on the experiences of key actors in a feminist Civil Society Organization (CSO) and a newly professional women's team, respectively, we examine what the pandemic has meant for women's football and for women football players at different levels of the game. We also consider the potential impact of the current situation on the future of women's football in Argentina, representative of wider social advances for women in the country.